ANALISIS TINGKAT KEPATUHAN WAJIB PAJAK ORANG PRIBADI TERHADAP TINGKAT PENERIMAAN PAJAK DI KABUPATEN LAHAT - Dewi Rina Komarawati; - Mukhtaruddin (InFestasi, 2012)
This study aims to  determine the level of complience of Personal Income Tax taxpayers in submitting the report of annual tax income to the Primary Tax Office of Lahat Regency and to determine whether the number of taxpayers who have tax ID number increased  significantly along with the increasing of Personal Income Tax Revenue in Lahat regency.The result shows that the number of individual taxpayers in Primary Tax Office of Lahat Regency was increasing during the observed years, however while the number of taxpayer who submitted its Annual Return was not as many as the number of individual taxpayer and it intended to decrease. In addition, it is found that the tax payer compliance has not significant affect to individual income tax receipts. To improve the performance of the Primary Tax Office of Lahat Regency in gathering individual income tax receipt, it is suggested that the office needs to socialize about the benefit and importance of having a Tax ID number to citizens and gives rewards and apreciation on the taxpayers compliance.